2022
DOI: 10.3390/cells11213378
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Glycoprotein YKL-40 Is Elevated after Coronary Artery Bypass Surgery and Correlates with Leukocyte Chemotaxis and Myocardial Injury, a Pilot Study

Abstract: The aim of the present study was to investigate the levels of YKL-40 during and after coronary artery bypass grafting surgery (CABG) and to establish possible connections between YKL-40 and markers of oxidative stress, inflammation, and myocardial injury. Patients undergoing elective CABG utilizing cardiopulmonary bypass (CPB) were recruited into the study. Blood samples were collected at the onset of anesthesia, during surgery and post-operatively. Levels of YKL-40, 8-isoprostane, interleukin-8 (IL-8), monocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Our results showed that plasma IL-2 levels started to increase as soon as surgical trauma began and progressed thereafter but apparently it does not play a regulatory role in the mobilization of CD117 + cells; its increase is most probably secondary to its essential role in immune tolerance, generation of effector and memory cells and Treg cells development [39,40] and the need to minimize immunosuppression and immune cells dysfunction in any cardiac surgery procedure [41,42]. Interleukin 8 concentration peaked as the grafting procedure initiated; it has been clearly established that this leukocyte chemotactic cytokine is clearly associated with in ammation and brosis following coronary artery bypass surgery [43] as it recruits neutrophils into injured myocardium [44]. It is important to mention that interleukin 8 up regulates the expression of CXCR7 [45] and the latter plays a role in hematopoietic stem cells homing via SDF1a gradient as it is considered a mediator of the CXCR4/SDF1a axis [14].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that plasma IL-2 levels started to increase as soon as surgical trauma began and progressed thereafter but apparently it does not play a regulatory role in the mobilization of CD117 + cells; its increase is most probably secondary to its essential role in immune tolerance, generation of effector and memory cells and Treg cells development [39,40] and the need to minimize immunosuppression and immune cells dysfunction in any cardiac surgery procedure [41,42]. Interleukin 8 concentration peaked as the grafting procedure initiated; it has been clearly established that this leukocyte chemotactic cytokine is clearly associated with in ammation and brosis following coronary artery bypass surgery [43] as it recruits neutrophils into injured myocardium [44]. It is important to mention that interleukin 8 up regulates the expression of CXCR7 [45] and the latter plays a role in hematopoietic stem cells homing via SDF1a gradient as it is considered a mediator of the CXCR4/SDF1a axis [14].…”
Section: Discussionmentioning
confidence: 99%